Feeder-Cell-Free and Serum-Free Expansion of Natural Killer Cells Using Cloudz Microspheres, G-Rex6M, and Human Platelet Lysate - Johnson, Christopher D. L.; Zale, Nicole E.; Frary, Eric D.; Lomakin, Joseph A. (Frontiers in Immunology, 2022)
The versatility of natural killer cells has ignited growing interest in their therapeutic use for cancer and other immunotherapy treatments. However, NK cells compose a small portion of peripheral blood mononuclear cells (5-20% of PBMCs) and clinical doses require billions of cells. Manufacturing suitable doses of NK cells remains a major challenge for NK immunotherapy. The current standard for expanding NK cells relies on feeder cells and fetal bovine serum to achieve large expansion, but both encounter regulatory concerns. We developed NK Cloudz, a dissolvable polymer-based microsphere platform, as an alternative to a feeder cell approach to expand NK cells. We demonstrated that a combination of NK Cloudz, a G-Rex6M culture vessel, and GMP Human Platelet Lysate expanded NK cells 387 ± 100-fold in 10 days from a PBMC starting population. To our knowledge, this is the highest rate of expansion reported for a feeder-cell-free approach to date. The NK purity, viability, and cytotoxicity were similar to both a feeder cell protocol and an FBS-based protocol. Additionally, we found no significant differences between FBS and GMP Human Platelet Lysate and concluded that platelet lysate is a good xeno-free alternative to FBS for NK expansion. Overall, we demonstrated a feeder-cell-free and FBS-free protocol that leverages NK Cloudz as a promising step toward a commercial GMP manufacturing method to expand NK cells for therapeutic use.